Identifikasi Karakteristik Gaya Belajar - Nursyam; Jeihn Novita C. Budiman; Avera Linarti (Politeknik Pelayaran Barombong, 2021)
The background of the study concluded that previous cadets had difficulty getting optimal test results, so the researchers assumed this problem was related to the difficulty of cadet in absorbing subject matter provided by lecturers or instructors, where they had not used adjustments to teaching methods with the tendency of cadets' learning styles. The research aims to describe the learning styles of cadets of Politeknik Pelayaran Barombong class of 64 years of 2020-2022 training. This study is a qualitative study to describe the learning styles of class 64 cadets. Respondents were all cadets of class 64 who met the research criteria, totaling 153 cadets. The research instrument used the VARK version.8.0 test which has been translated into Indonesian and analyzed using a percentage form which describes the frequency characteristics of the cadets' learning styles. The learning styles of cadets studied in this study were visual learning styles, auditory learning styles, reading learning styles and kinetic learning styles. Through this research, it was found that the learning style of cadets class 64 which was the most dominant was the kinesthetic learning style with a percentage of 51.6% of the total research respondents